2018
DOI: 10.1038/s41435-018-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants at the 16p13 locus confer risk for eosinophilic esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a chronic inflammatory disease of the esophagus triggered by immune hypersensitivity to food. Herein, we tested whether genetic risk factors for known, non-allergic, immune-mediated diseases, particularly those involving autoimmunity, were associated with EoE risk. We used the high-density Immunochip platform, encoding 200,000 genetic variants for major auto-immune disease. Accordingly, 1,214 subjects with EoE of European ancestry and 3,734 population controls were genotyped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 96 publications
0
16
0
1
Order By: Relevance
“…[18][19][20] In single studies genome-wide significant associations have also been found at 19q13 (ANKRD27) and 16p13 (CLEC16A). 21 Furthermore, an interplay of gene-gene (particularly between IL4 and TSLP) and gene-environment interactions have been shown to be contributory. 5,22,23 In a phenome-wide association study approach, a set of genetic variants are assessed in the context of many phenotypes.…”
Section: Common Eoe Genetic Risk Locimentioning
confidence: 99%
“…[18][19][20] In single studies genome-wide significant associations have also been found at 19q13 (ANKRD27) and 16p13 (CLEC16A). 21 Furthermore, an interplay of gene-gene (particularly between IL4 and TSLP) and gene-environment interactions have been shown to be contributory. 5,22,23 In a phenome-wide association study approach, a set of genetic variants are assessed in the context of many phenotypes.…”
Section: Common Eoe Genetic Risk Locimentioning
confidence: 99%
“…Reports from this collaboration thus far have identified a number of putative susceptibility loci for EoE and elucidated a likely role of CAPN14 (encoding calpain 14, a calcium-activated cysteine protease) in the tissue-specificity and allergic disease-linked aspects of the disorder 19 and risk loci at 16p13 that links EoE with 10 other immune-associated diseases. 20 These various findings provide clinical insights and a means to reach better diagnostic and therapeutic outcomes.…”
Section: Cofar Eosinophilic Esophagitis Registrymentioning
confidence: 99%
“…The recent development of esophageal organoids 18 provides a novel experimental framework to eventually decipher the mechanisms of these gene-gene interactions. The role of other recently identified EoE susceptibility loci, such as 16p13 (likely related to the CLEC16A gene), 16 will be an important line of future research.…”
Section: Eoementioning
confidence: 99%
“…A number of new genetic risk factors have been identified for EoE. 15,16 Many of these risk factors are present in genes encoded for by esophageal epithelial cells, and evidence is emerging that the critical disease pathogenesis is related to epithelial cell dysfunction and loss of epithelial cell differentiation. 13 A key dilemma remains because these genetic associations might be driven by the underlying atopic disease also present in EoE cohorts.…”
Section: Eoementioning
confidence: 99%